Factores bioquimicos del aprendizaje - Ardila, Ruben (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
This article presents the principal work done on the influence of biochemical factors on learning. Importance is given to the research of Hyden on RNA, of Rosenzweig, Krech and Bennett on acetylcholine and Cholinesterase, and of Plotnikoff and Cameron on pemolino de magnesio. Emphasis is put on the areas that should still be investigated with an end to obtaining a coherent picture of the biochemical foundations of learning.